2022
DOI: 10.17323/jle.2022.13339
|View full text |Cite
|
Sign up to set email alerts
|

EFL University Students’ Self-Regulated Writing Strategies: The Role of Individual Differences

Abstract: Background. Self-regulated learning strategies play an essential role in the success of students’ learning of writing. The use of these strategies might be influenced by the student’s individual differences. Purpose. This study was conducted to describe EFL university students’ preferences for self-regulated writing strategies. It also examined the different use of self-regulated writing strategies by considering gender, interest in English writing, and writing achievement. Further, it measured the predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The results of Mirovic and Knezevic (2018) and the current study explored the details of strategies and self-efficacy (SE), except for the affective domain in the Bloom Digital Taxonomy (BDT). Using the findings of recent studies (Wardhana, 2022;Umamah et al, 2022;Nikcevic-Milkovic et al, 2022;Yicai & Xueai, 2021;Blankenstein et al, 2019;Mirovic & Knezevic, 2018), it was concluded that self-efficacy (SE) has been examined from different perspectives and the current study adds new insights to existing knowledge of the Bloom Digital Taxonomy (BDT).…”
Section: Research Papersmentioning
confidence: 87%
See 2 more Smart Citations
“…The results of Mirovic and Knezevic (2018) and the current study explored the details of strategies and self-efficacy (SE), except for the affective domain in the Bloom Digital Taxonomy (BDT). Using the findings of recent studies (Wardhana, 2022;Umamah et al, 2022;Nikcevic-Milkovic et al, 2022;Yicai & Xueai, 2021;Blankenstein et al, 2019;Mirovic & Knezevic, 2018), it was concluded that self-efficacy (SE) has been examined from different perspectives and the current study adds new insights to existing knowledge of the Bloom Digital Taxonomy (BDT).…”
Section: Research Papersmentioning
confidence: 87%
“…The results showed that the genre-based approach (GBA) improved academic writing proficiency and self-efficacy (SE), therefore, the current study perpetuated this suggestion. Umamah et al (2022) showed the use of self-regulated writing (SRW) procedures to enhance writing outcomes. The results confirmed the importance of SRW strategies and explained individual differences, while the current study seeks otherwise.…”
Section: Research Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the predictive effects of self-regulated writing strategies on writing performance have also been widely explored [ 20 , 23 , 24 , 67 ]. Teng and Zhang’s study [ 20 ] revealed some strategies, such as text processing in the cognitive dimension; idea planning and goal-oriented monitoring and evaluating strategies in the metacognitive dimension; and emotional control and motivational self-talk in the motivational regulation dimension, strongly affect learners’ writing outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, studies on language proficiency and genders have been inconclusive. Qin and Zhang [ 27 ] and Teng, Wang, and Zhang [ 28 ] found significant differences among EFL learners at different language proficiency levels in China, while Mallahi [ 71 ] and Umamah, Khoiri, Widiati, and Wulyani [ 67 ] found that language proficiency levels did not significantly influence L2 learners’ self-regulated writing strategies in EFL contexts in Iran and Indonesia. Teng, Wang, and Zhang found that female learners used more self-regulatory writing strategies than male students did, while Shen and Bai [ 24 ] found that gender and academic major were not mediating factors that influenced L2 learners’ self-regulated writing strategies.…”
Section: Literature Reviewmentioning
confidence: 99%